Measurement of Intrapreneurial Behavior In Mexican Trade Sector Companies (Journal of Business, Universidad del Pacífico (Lima, Peru), 2022)
Currently, the topic of entrepreneurship seeks to understand entrepreneurial activity and the factors behind the generation of entrepreneurial activities. However, during the last decade a new construct known as corporate entrepreneurship (CE) or intrapreneurship (IE) is considered as a concept applied in different contexts and is not yet developed thoroughly within organizations. The objective of the study is to determine the validity of a measurement instrument, whose unit of analysis is focused on employees working in companies of the trade sector in the municipality of Ensenada, Baja California, Mexico, specifically aimed at administrative employees, middle and upper management in trade companies. For the content validity, a review by seven experts was applied, followed by a pilot test with a representative sample of 30 middle management employees, then a factor analysis and the validity of Cronbach's Alpha were developed using the Statistical Package for the Social Sciences (SPSS) version 25 software, resulting in the fulfillment of the criteria of both validity and reliability in the survey applied.Video abstract (spanish): https://www.youtube.com/watch?v=c9Gisj_pWMU&t=2s
Keywords: Content Validity; Construct Validity; Intrapreneurship; Organizational Factors; Intrapreneurial Behavior; Trading Companies